PENINGKATAN KEMAMPUAN MENULIS TEKS PROSEDUR MENGGUNAKAN TEKNIK 3M PADA SISWA SMPN 3 SUNGAI BETUNG - Angie, Lovera Bani; Syambasril, Syambasril; Ramdani, Deden (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to describe the planning, implementation, the learning outcomes in writing procedure text instruction using the 3M (observing, imitating, adding) technique. This is a classroom action research on class VII students of SMPN 3 Sungai Betung, conducted in two cycles. The research method used was descriptive in the form of qualitative research. Data were analyzed qualitatively to determine the achievement level of learning outcomes in quantitative form using a simple statistical method. The findings showed that the 3M technique improved the students? learning outcomes. (1) The planning in cycles I and II was in accordance with the steps in the selected technique; However, one step of the technique had not been included in the lesson plan and had been revised in cycle II. (2) The implementation in cycle I had run well; However, one of the learning steps in the lesson plan had not been done and had been revised in cycle II. (3) The learning outcomes, as seen from the average of the test in cycles I and II improved from 59.5 to 71.6. Therefore, improvement in further research is highly concerned to enhance the teaching and learning process and to discover innovations in writing skills. Keywords: Writing Procedure Text, 3M technique (observing, imitating, adding), Class Action Researc